2001
DOI: 10.4049/jimmunol.167.1.264
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor NF-κB Regulates Igλ Light Chain Gene Rearrangement

Abstract: The tissue- and stage-specific assembly of Ig and TCR genes is mediated by a common V(D)J recombinase complex in precursor lymphocytes. Directed alterations in the accessibility of V, D, and J gene segments target the recombinase to specific Ag receptor loci. Accessibility within a given locus is regulated by the functional interaction of transcription factors with cognate enhancer elements and correlates with the transcriptional activity of unrearranged gene segments. As demonstrated in our prior studies, rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…By mapping in vivo targets of p65 through ChIP, we found that p65 binds proximal to 5Ј ends, as expected, but also with a high frequency at many other sites, including introns and sites distal to 5Ј ends. Finding NF-B-binding sites in introns is not unexpected because it was originally identified by its binding an enhancer element in the first intron of the light chain gene; since then, several examples of NF-B to binding intronic sequences have emerged (22,23,28,29). Our data also indicate that p65 not only binds genes whose expression is regulated by the proinflammatory cytokine TNF-␣ but also binds a large number of genomic loci whose expression is not regulated.…”
Section: Discussionsupporting
confidence: 50%
“…By mapping in vivo targets of p65 through ChIP, we found that p65 binds proximal to 5Ј ends, as expected, but also with a high frequency at many other sites, including introns and sites distal to 5Ј ends. Finding NF-B-binding sites in introns is not unexpected because it was originally identified by its binding an enhancer element in the first intron of the light chain gene; since then, several examples of NF-B to binding intronic sequences have emerged (22,23,28,29). Our data also indicate that p65 not only binds genes whose expression is regulated by the proinflammatory cytokine TNF-␣ but also binds a large number of genomic loci whose expression is not regulated.…”
Section: Discussionsupporting
confidence: 50%
“…The cycling profile for J2͞3 SEs has been described (22). D␤ SE and RE cycling profiles were 94°C, 30 s; 62°C, 30 s; and 72°C, 30 s. A 2-l sample of PCR1 was used as template in 27-cycle (SE assays) or 30-cycle (RE assays) PCRs with nested primers.…”
Section: Methodsmentioning
confidence: 99%
“…Primers used in assays for 5ЈJ2͞3 SEs (22), VJ coding joins, J␤C transcripts, C, and ␤-actin have been described (12). Additional primers and probes are as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, NF-B-binding sites are present in the human and mouse IgH, Ig, and Ig enhancer modules (15)(16)(17)(18)(19)(20). Different studies using mice or murine B cell lines have shown that impairing NF-B function-either by knocking down/repressing its component subunits or by increasing IB␣ expression-has dramatic effects on the level of Ig gene rearrangement (21)(22)(23). In vitro studies have demonstrated that the RAG proteins are critical in the joining phase of recombination and interact with the postcleavage coding ends (24).…”
mentioning
confidence: 99%